Bat algorithm for rough set attribute reduction - Taha A.M.; Tang A.Y.C. (Asian Research Publishing Network (ARPN), 2023)
Attribute reduction (AR) refers to the problem of choosing an optimal subset of attributes from a larger set of possible attributes that are most predictive for a given result. AR techniques have recently attracted attention due to its importance in many areas such as pattern recognition, machine learning and signal processing. In this paper, a new optimization method has been introduced called bat algorithm for attribute reduction (BAAR), the proposed method is based mainly on the echolocation behavior of bats. BAAR is verified using 13 benchmark datasets. Experimental results show that the performances of the proposed method when compared to other features selection methods achieve equal or better performance. 2005 - 2013 JATIT & LLS. All rights reserved.